Potential role for vitamin D vs. intermittent fasting in controlling aquaporin-1 and aquaporin-3 expression in HFD-induced urinary bladder alterations in rats - Hassan, Hend M.; El-Gamal, Randa; Hamed, Walaa. H. E.; Habotta, Ola Ali; Samy, Mervat; Elmowafy, Rasha; ElNashar, Eman Mohamed; Alghamdi, Mansour Abdullah; Aldahhan, Rashid A.; Al-Khater, Khulood Mohammed; Alshehri, Mohammed A.; Ahmed, Magda E. (Frontiers in Molecular Biosciences, 2024)
Background: High-fat diet-induced obesity is linked to suppression of aquaporins (AQPs) expression in different tissues. Both vitamin D and intermittent fasting were identified to enhance AQPs expression. In the urinary bladder, AQP1 and AQP3 mRNA transcripts were identified. Vitamin D has an impact on a variety of genes that encode proteins that control cell proliferation, differentiation, and death. Aim: To assess potential benefits of vitamin D and intermittent fasting (IF) and to explore alterations to the urinary bladder triggered by high-fat diet (HFD) in a rat model of obesity. Methods: Each of the 4 groups contained six adult male albino rats; control: a standard rodent chew for 12 weeks, HFD: HFD and fructose were administered orally via gastric gavage for 12 weeks, and vitamin D: HFD and fructose were administered orally for 8 weeks, then 4 weeks of intraperitoneal injection of vitamin D (5 microns /Kg /2 days) and IF group: Received intraperitoneal injections of vitamin D (5 microns / Kg/ 2 days) for 4 weeks after consumption of HFD and fructose orally for 8 weeks. The serum lipid profile was conducted at end of the experiment. In the bladder homogenates, the levels of oxidative stress indicators were assessed. Quantitative real-time PCR was performed on recently collected bladder samples. AQP1 and AQP3 immunohistochemistry was done. Results: When compared to the HFD group, the vitamin D and IF groups both demonstrated a substantial improvement in histopathological, immunohistochemical, biochemical, and molecular markers. Conclusion: In all examined parameters, IF exceeded vitamin D as a preventive factor for the urinary bladder deterioration.